2018
DOI: 10.1080/14017431.2018.1430372
|View full text |Cite
|
Sign up to set email alerts
|

Early repolarization pattern in the coronary slow flow phenomenon

Abstract: We report that CSFP is associated with J-wave and slurring ERPs. However, the clinical significance of these changes needs to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Patients with CSF experience unexplained recurrent chest pain symptoms (7)(8)(9). Myocardial ischemia and acute coronary syndrome can occur in patients with severe CSF (10,11), which results in a higher incidence of sudden death caused by acute myocardial infarction and ventricular arrhythmia among these patients (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CSF experience unexplained recurrent chest pain symptoms (7)(8)(9). Myocardial ischemia and acute coronary syndrome can occur in patients with severe CSF (10,11), which results in a higher incidence of sudden death caused by acute myocardial infarction and ventricular arrhythmia among these patients (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…17 Sucu M et al 18 in a study reported an association between the J-wave and slurring early repolarization pattern with coronary slow flow phenomenon among patients with positive responses to treadmill testing or chest pain indicative of "stable angina" pectoris. In a different investigation conducted by Kitamura T and colleagues, 19 it was observed that the existence of early repolarization patterns, particularly when they exhibit day-to-day fluctuations, can serve as a valuable predictor for the recurrence of ventricular fibrillation (VF) in individuals with vasospastic angina (VSA). Consequently, for the secondary prevention of VF in high-risk VSA patients, the implantation of an "implantable cardioverter defibrillator (ICD)" is considered a reasonable strategy.…”
Section: Discussionmentioning
confidence: 99%
“…CSF refers to a phenomenon whereby normal or nearnormal major branches of the coronary arteries are observed on coronary angiography but there is delayed blood flow in distal blood vessel upon imaging [2][3][4]. ere is now substantial evidence demonstrating that CSF is a main cause of clinical cardiovascular events such as resting and exertional angina and even myocardial infarction [2,[23][24][25], which severely affect quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…is phenomenon is termed coronary slow flow (CSF), which refers to normal or nearnormal major branches in the coronary arteries on coronary angiography but delayed and slow distal blood flow in vessel imaging [2][3][4]. CSF has been increasingly recognized with the popularization of coronary angiography, and it occurs in approximately 7% of patients with suspected coronary heart disease [5].…”
Section: Introductionmentioning
confidence: 99%